2023
DOI: 10.3390/endocrines4020034
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hypothalamic Neuropeptides in Regulation of Liver Functions in Health and Disease

Abstract: The communication between brain and peripheral tissues is mediated by neuropeptides that coordinate the functions of each organ with the activities of the entire body in specific environmental conditions. Hypothalamic neuropeptides act as neurotransmitters and hormones to regulate the physiology of food intake, digestion, and metabolism, having a direct or indirect impact on the liver. Investigations on liver pathologies found that dysfunctions of neuropeptides and their receptors are associated with liver dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 239 publications
0
1
0
Order By: Relevance
“…NPY and AgPR are primarily known for their orexigenic effects, as they are potent and long-lasting appetite stimulators. They act to promote food intake and energy storage, particularly during times of negative energy balance or stress [ 41 ]. It has been shown that NPY is involved in the control of both food intake and GH secretion [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…NPY and AgPR are primarily known for their orexigenic effects, as they are potent and long-lasting appetite stimulators. They act to promote food intake and energy storage, particularly during times of negative energy balance or stress [ 41 ]. It has been shown that NPY is involved in the control of both food intake and GH secretion [ 42 ].…”
Section: Discussionmentioning
confidence: 99%